Brand Personality and Generation Y Purchase Intention Of Halal Fast Food Restaurants In Pahang - Ida Rizyani, Tahir; Mazita, Mokhtar; Azizan, Azit; Wan Khairul Anuar, Wan Abd Manan; Khairun Aisyah, Mohammad (2017)
In this modern competitive environment, many brands are available for the consumers to choose, which provide similar kind of benefits. In current scenario brand personality is very important for the companies to position their brand in the market. It is very important to differentiate our offerings from those of the competitors. In this context, brand personality plays an important role to identify and differentiate the product as companies increasingly enter and exit the market. Brand personality can be defined as the set of personality traits of human which are attributed to a brand. The purpose of this study is to categorise the important dimensions of brand personality among generation Y. The study adopted quantitative method and questionnaires being distributed randomly The results of this study shows that sincerity is the most important dimension of brand personality which affect the purchase intention of young consumers.